2020
DOI: 10.1101/2020.05.21.109470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and reconstitution of a hydrolase complex that releases peptidoglycan from the membrane after polymerization

Abstract: Bacteria are surrounded by a peptidoglycan cell wall that is essential for 17 their survival 1 . During cell wall assembly, a lipid-linked disaccharide-peptide 18 precursor called Lipid II is polymerized and crosslinked to produce mature 19 peptidoglycan. As Lipid II is polymerized, nascent polymers remain membrane-20 anchored at one end and the other end becomes crosslinked to the matrix 2-4 . A 21 longstanding question is how bacteria release newly synthesized peptidoglycan 22 References: 332 333

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…16 Transporter proteins flip the extended WTA polymer to the extracellular surface, 17 where it is linked to PG. 6,18 D-Alanylation of ribitol units is thought to occur extracellularly and is mediated by the DltA, DltB, DltC, and DltD proteins. 19 Lipoteichoic acid (LTA) is also produced by Gram-positive bacteria but is integrally associated with the cell membrane.…”
mentioning
confidence: 99%
“…16 Transporter proteins flip the extended WTA polymer to the extracellular surface, 17 where it is linked to PG. 6,18 D-Alanylation of ribitol units is thought to occur extracellularly and is mediated by the DltA, DltB, DltC, and DltD proteins. 19 Lipoteichoic acid (LTA) is also produced by Gram-positive bacteria but is integrally associated with the cell membrane.…”
mentioning
confidence: 99%
“…24−26 Additionally, WTA recruits PBP4 to the cell division septum, which allows PBP4 to participate in β-lactam resistance. 2,3,31,54 Because WTA synthesis is essential for a robust cell wall architecture, 55 previous studies that disrupt WTA biosynthesis with mutants were not accurately representing the MRSA cell wall. Furthermore, disrupting WTA biosynthesis causes biomolecular precursors and Lipid II fragments to accumulate, which downregulates vital biochemical pathways.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Furthermore, disrupting WTA biosynthesis causes biomolecular precursors and Lipid II fragments to accumulate, which downregulates vital biochemical pathways. 55 To avoid these confounding variables, we used wild-type MRSA cells (which have a completely intact envelope composition and architecture) to investigate the role of WTA in cell division and β-lactam resistance. We found that hydrophilic, amineterminated, 600 Da branched polyethylenimine (BPEI) binds to and disables WTA within wild-type MRSA cells.…”
Section: ■ Conclusionmentioning
confidence: 99%